Linking Local Government Discretion and Accountability in Decentralisation - Yilmaz, Serdar; Beris, Yakup; Serrano-Berthet, Rodrigo (2012)
Decentralisation offers significant opportunities to improve government accountability by exerting stronger pressures both from below (demand) and above (supply). The literature contains many examples, however, where the potential has not been realised, partly because decentralisation reforms have often been introduced without thinking through their accountability implications. Even when accountability is taken into account, the efforts tend to emphasise either the supply or the demand side of the equation, but not both. Drawing on the sets of literature on fiscal, administrative and political decentralisation, this article presents a methodology for studying this.